The influence of brand image and sales promotion on purchasing decisions mediated by trust (Empirical study of Sunyi, House of Coffee & Hope Jakarta) - Yapputra, Evan; Dahlan, Kandi Sofia Senastri (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to examine the influence of Brand Image and Sales Promotion on Purchase Decisions mediated by Trust. The research involved 173 respondents who had made purchases at Sunyi, House of Coffee & Hope Jakarta. Data collection was conducted using an online questionnaire. The analytical method used is Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results of this study indicate that Brand Image and Sales Promotion have a positive and significant impact on Trust. Additionally, Brand Image and Sales Promotion also positively and significantly affect Purchase Decisions. Trust positively and significantly influences Purchase Decisions and partially mediates the effect of Brand Image and Sales Promotion on Purchase Decisions. This research provides empirical evidence that Brand Image and Sales Promotion are crucial factors in building Trust and influencing Purchase Decisions among consumers at Sunyi, House of Coffee & Hope Jakarta. The managerial implications of this study highlight the importance for Sunyi, House of Coffee & Hope Jakarta to continuously build a positive Brand Image and enhance effective Sales Promotion strategies to strengthen consumer Trust and drive Purchase Decisions.